Copper Trafficking in Plants and Its Implication on Cell Wall Dynamics - Printz, Bruno; Lutts, Stanley; Hausman, Jean-Francois; Sergeant, Kjell (Frontiers in Plant Science, 2016)
In plants, copper (Cu) acts as essential cofactor of numerous proteins. While the definitive number of these so-called cuproproteins is unknown, they perform central functions in plant cells. As micronutrient, a minimal amount of Cu is needed to ensure cellular functions. However, Cu excess may exert in contrast detrimental effects on plant primary production and even survival. Therefore it is essential for a plant to have a strictly controlled Cu homeostasis, an equilibrium that is both tissue and developmentally influenced. In the current review an overview is presented on the different stages of Cu transport from the soil into the plant and throughout the different plant tissues. Special emphasis is on the Cu-dependent responses mediated by the SPL7 transcription factor, and the crosstalk between this transcriptional regulation and microRNA-mediated suppression of translation of seemingly non-essential cuproproteins. Since Cu is an essential player in electron transport, we also review the recent insights into the molecular mechanisms controlling chloroplastic and mitochondrial Cu transport and homeostasis. We finally highlight the involvement of numerous Cu-proteins and Cu-dependent activities in the properties of one of the major Cu-accumulation sites in plants: the cell wall.